Steamboats and the Rise of the Cotton Kingdom - Gudmestad, Robert H., 1964- (Book collections on Project MUSE., 2011)
In Steamboats and the Rise of the Cotton Kingdom Robert Gudmestad offers new insights into the remarkable and significant history of transportation and commerce in the antebellum South. He examines the wide-ranging influence of steamboats on the Southern economy. From carrying cash crops to market, to contributing to slave productivity, increasing the flexibility of labor, and connecting southerners to overlapping orbits of regional, national, and international markets, steamboats not only benefitted slaveholders and northern industries but also affected cotton production.